Polymorphisms of histone deacetylase 1 and 3 genes and fatty acid binding protein 3 and 4 genes and their associations with economic traits in swine - Ye, X.; Robinson, J.A.B.; Jiang, Z.; Gibbins, A.M.V.; Gibson, John P. (Institut National de la Recherche Agronomique, 2002)
A resource population of 429 pigs was developed from crosses of Hampshire, Duroc and Large White breeds ((H x D) x LW) for detection of quantitative trait loci (QTLs). Associations of histone deacetylase (HDAC) and fatty acid binding protein (FABP) candidate genes with 110 growth, carcass and meat quality traits were investigated. It was shown that there were significant associations between loci in HDAC 1 (Hinf I site) and in HDAC 3 (Tsp509 I site) and weight of picnic fat, jowl and hock or weight of butt internal fat, chub fat and trimmed belly, respectively. An Msp I locus in FABP 3 was significantly associated with body weight and hock weight and a Bsm I locus in FABP 4 was significantly associated with intramuscular fat percentage and picnic skin weight.